BRAZIL-CHINA RELATIONS UNDER LULA AND BOLSONARO: RAPPROCHEMENT AND DISTANCING THROUGH DISCOURSE - Duarte, Paulo Afonso Brardo; Braga Dutra, Lucas (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
This article aims to provide a comparative analysis of Sino-Brazilian relations from the Brazilian perspective during the presidencies of Luiz Inácio Lula da Silva and Jair Messias Bolsonaro. This analysis is based on the examination of speeches made by both presidents during their respective terms. Drawing on the French tradition of Discourse Analysis, the study seeks to comprehend how the two presidents behaved in the context of the Brazil-China relationship throughout their respective terms. This study is based on the hypothesis that there was a desire to bring the relationship between the two countries closer during Lula’s administration and an attempt to distance it, at least in President Bolsonaro’s informal speeches, which was not, however, corroborated by his formal speeches.